Effect of Nitrogen Sources on Yield, Fruit Quality and Nutritional Status of Apple (Malus×Domestica Borkh.) - Jeet, Amar; Sharma, N. C.; Chandel, J. S. (International Journal of Bio-resource and Stress Management, 2016)
A trial was conducted in a private orchard at Matiyana (Shimla), India (during December, 2014 to December, 2015) to find out the alternate to calcium ammonium nitrate for nitrogen application to apple trees. Different nitrogen containing fertilizers (sources of nitrogen) alone or in combination were used as treatments and applied in split doses to the experimental trees. Different nitrogen sources significantly influenced fruiting, yield, fruit quality and leaf nutrient contents of apple. Trees subjected to calcium nitrate+urea treatment exhibited significantly higher fruit set (23.96%), yield (5.20 kg tree-1) as well as yield efficiency (0.183 kg cm-2 trunk cross sectional area (TCSA) and lower fruit drop (13.06%). The treatment (calcium nitrate+urea) significantly improved fruit weight (179.67 g), total soluble solids content (13.10 °B), total sugars (9.99%) and reducing sugars content (7.15%). Similarly, significantly higher leaf N (2.86%), K (1.93%) and Mg (0.44%) contents were recorded in trees subjected to calcium nitrate+urea treatment, whereas, leaf P (0.28%) and Ca (1.58%) were observed highest in trees treated with combination of di-ammonium phosphate and calcium nitrate and calcium nitrate, respectively. With respect to various observations recorded, calcium nitrate+urea treatment was either superior or statistically at par with calcium ammonium nitrate (control), thus calcium nitrate+urea was proved to be most suitable alternate to calcium ammonium nitrate for supplying nitrogen to the apple trees.